Blended Learning Activities in an e-Business Course - Jirarat Sitthiworachart; Mike Joy; Jon Mason (My University, 2021)
The objectives of this study were threefold: to understand students’ perceptions of activities in a blended learning environment; to determine their preferred learning activities in this context, paralleling the four stages of Kolb’s learning cycle; and to determine the effectiveness of the blended learning used, based on scores achieved in an e-business course supported by the BLearning assessment system, a custom-designed reflective assessment tool. A mixed-methods approach was used to identify the students’ preferred activities. Findings indicate that (1) blended learning can add interest and variety to improve the students’ learning experience, (2) students prefer blended learning activities that match the first three stages of Kolb’s learning cycle (concrete experience, reflective observation, and abstract conceptualisation), and (3) data collected from the e-business course exam results show that the blended learning process was effective. In aligning teaching activities to student preferences, the notion of “teaching patterns” is introduced as the teaching perspective on these activities. Findings further indicate that blended learning activities based on the first three stages of Kolb’s learning cycle may be more suitable for students who share similar learning preferences.
Keywords: Blended Learning; Learning cycle; Online and Blended Learning